The Potential of Phosphorus Nitride Monolayer for Li–S Battery from the Anchoring and Diffusing Perspective: A First‐Principles Study. Issue 3 (6th December 2021) - Zheng, Xinyi; Lin, Shiru; Kong, Dalin; Wei, Yadong; Pang, Kaijuan; Ku, RuiQi; Kaner, Ngeywo Tolbert; Xu, Xiaodong; Sha, Ming; Liu, Jinhong; Huang, Hongxi; Yang, Jianqun; et al.
Abstract: The performance of lithium–sulfur (Li–S) battery is strongly dependent on the sulfur electrodes materials. Due to the chemical interaction between electrodes and intermediates produced in charging and discharging process, the Janus‐polar two dimensional (2D) electrode materials can enhance the electrochemical performance of Li–S battery by overcoming shuttle effect and increasing diffusion rates. Here, it is explored the structural, electronic, and dynamic characteristics of Li ion, S8 cluster, and lithium polysulfides adsorbed over Janus Phosphorus Nitride monolayer with blue phosphorene phase (b‐PN) by using first‐principles calculations. The reported findings highlight potential of the b‐PN monolayer as a good host material, given that the large absorption energies of different clusters vary from −0.47 to −3.78 eV, which can suppress shuttle effect effectively. These strong adsorptions are origin from the chemical interaction between nitrogen atoms of the b‐PN and Li atoms in lithium polysulfides in present work. Particularly, it is predicted that b‐PN monolayer has extremely small diffusion barriers for Li ion and Li2 S8 clusters of 0.10 and 0.03 eV, which leading to a higher battery charge and discharge rate than reported graphene and MoS2 . It is hoped that this efficient strategy for promising host materials of sulfur‐electrode guides the development of next‐generation lithium–sulfur batteries. Abstract : Lithium sulfur battery has an overwhelming advantage in energy density compared to traditional Li‐ions battery. This work focuses on a strategy of effectively inhibiting (Li–S) battery's "shuttle effect" by using b‐PN host‐nanomaterial to be sulfur composite electrode, so as to improve the cycling process and the (dis)charging rate.